Pengaruh Return on Asset (RoA), Return on Equity (RoE) dan Earning Per Share (EPS) Terhadap Harga Saham Perusahaan Makanan dan Minuman Pada Bursa Efek Indonesia Tahun 2020 - 2024 (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), and Earnings per Share (EPS) on the stock prices of food and beverage companies listed on the Indonesia Stock Exchange for the years 2020-2024, both partially and simultaneously. The sampling technique used is purposive sampling with a population size of 100. The sample of companies that meet the criteria is 50 companies. The data analysis method used is descriptive statistical analysis with statistics consisting of multiple linear regression analysis, coefficient of determination test (R2), partial T test, and simultaneous F test. The data from financial reports and stock prices obtained have been tested with classical assumption tests and the results can be used for regression data. Both simultaneously and partially, Return on Asset (ROA), Return on Equity (ROE), and Earnings per Share (EPS) significantly affect stock prices. Based on the coefficient of determination (R2) results, stock prices are influenced by ROA, ROE, and EPS by 66.4%, while the remainder is influenced by other variables discussed in the research